The evolution of Swedish fascism: self-identification and ideology in interwar Sweden. (19th October 2016) - Kunkeler, Nathaniël
ABSTRACT: Historians and social scientists generally understand nationalism to be the defining feature of fascism. Kunkeler's study challenges that assumption with his examination of Swedish fascist movements through the notion of self-identification. Using fascist periodicals, he traces the development of Swedish fascists' identification with the movement—in relation to matters of race, nation and the signifiers of 'fascism' and 'National Socialism'—from the early 1920s, when an overt attachment to Mussolini's project was evident, through a National Socialist phase showing cautious commitment to Nazi Germany, and ending with a final phase of strategic anonymity. In the face of criticism that fascism was an alien import, Swedish fascists adapted their public profile to accommodate such national sensitivities, developing a racialist ideology that was not confined by national borders and was believed to be more in tune with Swedish political culture at the time. When public opinion turned decisively against 'international fascism' in the mid-1930s, they were forced to discard the name and image of 'fascism' altogether and enter a final phase of public anonymity that, in any case, involved no significant ideological metamorphosis.